To Assess the Efficacy of Chemical Corneal Tattooing for Unsightly Corneal Scars - Irfan Shahzad, Sameera Irfan, Faiza Rashid (Pakistan Journal of Ophthalmology, 2014)
Purpose: To study the efficacy and safety of chemical corneal tattooing for unsightly corneal scars. Material And Methods: A prospective clinical study of 44 consecutive cases in the age range from 5 - 60 years was conducted at the oculoplastic department of Mughal Eye Trust Hospital, Lahore from June 2012 - Dec 2013. All patients desired a cosmetic treatment for their disfigured, white blind eye. After a complete ophthalmic examination and B scan ultrasound, and photographs of the patients’ eyes were taken. Chemical corneal tattooing was performed using 2% Gold Chloride and 2% Hydrazine Hydrate. Patients were followed up at the first, third and fifth post-operative day; then weekly for a month, at 3rd month, 6th month and 1st year post-operatively. Results: All patients had a mild red eye and discomfort in first few days but not afterwards. No corneal erosion or corneal melting was not noted in any case. Procedure had to be repeated in 5 cases (11.5%) after 3-6 months of the initial therapy. One year postoperatively, 42 cases (95.5%) were satisfied and asymptomatic; 2 cases (4.5%) were lost to follow-up. Conclusion: Chemical corneal tattooing is a simple, safe and an efficient technique yielding acceptable cosmetic results. Key words: Corneal tattoo, Corneal scar, Ocular trauma.